Design of Dry Cell HHO Generator using NaCl Solution for Hydrogen Production - Arif Budiman; Muhammad Yerizam; Yohandri Bow (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2022)
Excessive use of electricity produces emissions, as well as carbon will have impact on global warming because electricity mostly still using fossil-based energy. Usage of other alternative energy is beneficial to reduce dependence on the use of fossil fuels. Researchers are currently working to reduce the use of fossil energy by using renewable energy. Among the most common alternative energies found is water, so this research focuses on designing dry cell type HHO (Hydrogen Hydrogen Oxygen) Generator technology with hydrogen gas water electrolysis. The HHO generator functions to break water (H2O) into hydrogen atoms and oxygen atoms, known as HHO. Electrolysis testing using NaCl and a storage tube to see the rise and fall of water from the gas produced. NaCl used weighing 20 grams, 50 grams, 75 grams, and 100 grams dissolved in 500 cc of water. The results of the data obtained, many uses of NaCl produce hydrogen gas faster, the data shows 100 grams of NaCl at 180-210 seconds produces a gas volume of 175 CC compared to 20 grams produces a gas volume of 75 CC, 50 grams produces 125 CC, and 75 grams produces 150 CC